2017
DOI: 10.1002/cncr.30749
|View full text |Cite
|
Sign up to set email alerts
|

The association of demoralization with mental disorders and suicidal ideation in patients with cancer

Abstract: Clinically relevant demoralization frequently occurs independently of a mental disorder in patients with cancer and has a unique contribution to suicidal ideation. Demoralization is a useful concept to identify profiles of psychological distress symptoms amenable to interventions improving psychological well-being in this population. Cancer 2017;123:3394-401. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 44 publications
7
129
1
5
Order By: Relevance
“…Suicidal ideation occurs in both the demoralization/adjustment class and the severe psychiatric disorder class. This is consistent with recent studies of demoralization that revealed higher odds of suicidal ideation compared to anhedonic depression . Loss of meaning, hopelessness, worthlessness, and loss of control were also stronger mediators of a desire for hastened death than depressed mood .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Suicidal ideation occurs in both the demoralization/adjustment class and the severe psychiatric disorder class. This is consistent with recent studies of demoralization that revealed higher odds of suicidal ideation compared to anhedonic depression . Loss of meaning, hopelessness, worthlessness, and loss of control were also stronger mediators of a desire for hastened death than depressed mood .…”
Section: Discussionsupporting
confidence: 91%
“…In 3 systematic reviews, factors associated with demoralization included poor health, inadequately controlled physical or mental symptoms, reduced quality of life, unemployment and financial strain, reduced social functioning, single status, and social isolation or alienation . Furthermore, demoralization has a stronger association than depression with desire for hastened death and suicidal ideation .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this perspective, we found that social disconnection and demoralization, which encompasses the sense of failure, hopelessness, and loss of meaning, may reflect a relative failure of this mechanism to protect from existential distress in the terminally ill. Although demoralization has been associated with generalized anxiety and other mood disorders in palliative populations, the present study demonstrates a novel relationship between demoralization and death anxiety, two constructs which have been examined independently in previous research. In prior work, demoralization has also been associated with the desire for hastened death .…”
Section: Discussionmentioning
confidence: 55%
“…This means the findings are not conclusive for the entire palliative cancer care population, but are a good description of a particular population. Also, other relevant factors were not evaluated, such as dignity (Houmann, Chochinov, Kristjanson, Petersen, & Groenvold, 2014), demoralization (Vehling, Kissane, Lo, Glaesmer, Hartung et al, 2017), and spirituality (Delgado-Guay, Hui, Parsons, Govan, De la Cruz et al, 2011), which are important elements in the evaluation of patients with distress. In future studies, DHD should be evaluated by the semi-standardized approach using psychometric tools that allow comparisons between populations (Kremeike et al, 2018).…”
Section: Discussionmentioning
confidence: 99%